فعالية منهجية نموذج الهرم فعل المضارع في تحسين إتقان الفعل المضارع لدى طلاب الصف الثاني في سوبانغ جايا بولاية سلنجور - Che'Norizan, Nurul Aslina (SIBAWAYH Arabic Language and Education, 2025)
تسعى هذه الدراسة إلى تسهيل تمييز الطلاب لتصريف الفعل المضارع باستخدام نهج أكثر فعالية. الهدف العام من الدراسة هو مساعدة الطلاب على إتقان تصريف الفعل المضارع من خلال استخدام الصيغ وطرق التدريس الجذابة. تشمل الأهداف الخاصة للدراسة جعل الصيغ أداة مساعدة في التذكر وزيادة اهتمام الطلاب بعلم اللغة العربية. تشمل الدراسة 30 طالبًا من الصف الثاني من فصل 2 عمر عزيز في مادة اللغة العربية. تشمل المنهجية المستخدمة تخطيط العمل من خلال إنشاء ملاحظات وصيغ، وتنفيذ تطبيق إلكتروني يوفر ملاحظات وصيغًا وتدريبات تفاعلية. تم استخدام أسلوب اختبار ما قبل وما بعد لقياس فعالية النهج المتبع. أظهرت نتائج اختبار ما قبل مستوى منخفض من الإتقان في تصريف الفعل المضارع باستخدام الأسلوب التقليدي، حيث حصل اثنان فقط من الطلاب على درجات تتراوح بين 16-20. على العكس من ذلك، أظهرت نتائج اختبار ما بعد تحسنًا ملحوظًا بعد استخدام طريقة التدريس التفاعلية وصيغة هرم المضارع، حيث حصل عشرة طلاب على درجات تتراوح بين 16-20. تشير نتائج الدراسة إلى أن الطريقة التقليدية للتدريس التي تركز على الحفظ دون مشاركة نشطة من الطلاب أقل فعالية. على النقيض من ذلك، فإن النهج التفاعلي الذي يشرك الطلاب بنشاط واستخدام التكنولوجيا مثل التطبيقات الإلكترونية قد أثبت تحسين فهم الطلاب وإتقانهم لتصريف الفعل المضارع. إن استخدام أدوات المساعدة هذه يسهل عملية التعلم من خلال توفير وصول إلى مصادر أكثر تفاعلية وسهلة الوصول.الكلمات الرئيسية: تصريف الفعل المضارع، طرق التدريس، التطبيقات الإلكترونية، التعلم النشط This study aims to facilitate students in distinguishing the conjugation of the verb "fi'il mudhari'" using a more effective approach. The general objective of the study is to help students master the conjugation of "fi'il mudhari'" through the use of formulas and engaging teaching methods. Specific objectives include making formulas a memory aid and increasing students' interest in Arabic language studies, particularly the conjugation of "fi'il mudhari'." The study involves 30 students from Form 2 of Class 2 Umar Aziz in the Arabic language subject. The methodology includes action planning by creating notes and formulas, as well as implementing an electronic application that provides notes, formulas, and interactive exercises. The pre-test and post-test methods were used to measure the effectiveness of the applied approach. The pre-test results showed a low level of mastery in "fi'il mudhari'" using traditional methods, with only two students scoring between 16-20. In contrast, the post-test results showed a significant improvement after using the interactive teaching method and the Pyramid of Mudhari' formula, with ten students scoring between 16-20. The study concludes that traditional teaching approaches that focus on rote memorization without active student involvement are less effective. In contrast, interactive approaches that actively engage students and the use of technology such as electronic applications have proven to enhance students' understanding and mastery of "fi'il mudhari'". The use of these aids facilitates the learning process by providing access to more interactive and easily accessible resources. Keyword: Tasrif Feel Mudhari’, Teaching Methods, Electronic Applications, Active learning